2019
DOI: 10.2478/otmcj-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Accident at Construction Sites in Bangladesh

Abstract: Abstract Bangladeshi construction industry suffers more safety issues than other developing countries in the world. Among many of these, accidents at the construction site go far beyond and shape a horrific figure of death every year. The aims of this study are to identify and prioritize the causes of accidents. This study also analyses and discusses causes of accident at the construction site in Bangladesh. A widespread literature review and open discussion took place to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 55 publications
0
27
0
3
Order By: Relevance
“…This study analyzed types of injury and fatal accidents affected by OEQ based on thermal comfort. Most of the earlier works in previous research focused on a specific weather condition, such as those in summer and winter seasons [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. However, the results of this study showed that injury and fatal accidents in the spring and autumn seasons have greater probability than those of the summer and winter seasons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study analyzed types of injury and fatal accidents affected by OEQ based on thermal comfort. Most of the earlier works in previous research focused on a specific weather condition, such as those in summer and winter seasons [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. However, the results of this study showed that injury and fatal accidents in the spring and autumn seasons have greater probability than those of the summer and winter seasons.…”
Section: Resultsmentioning
confidence: 99%
“…A prevention method was presented to reduce injuries and incidents. Ahmed, 2019 [35] The author sought to identify the causes of accidents at construction sites in Bangladesh and established the interests of workers, owners, consultants and contractors through questionnaire surveys.…”
Section: Research Related To the Causes Of Construction Disastersmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the construction industry is increasingly becoming more knowledgeintensive (Nepal and Staub-French 2016) because the execution of construction activities requires higher levels of domain knowledge (specialized expert knowledge) (Serpella et al 2014). Many safety accidents have occurred due to the lack of domain knowledge (Ahmed 2019;Wong et al 2016). An elementary fragment of domain knowledge is called a domain knowledge element (DKE) (Durlach and Lesgold 2012).…”
Section: Introductionmentioning
confidence: 99%